Update on Oesophageal Atresia-Tracheoesophageal Fistula - Christophe Faure (Frontiers Research Topics, 2017)
Oesophageal atresia-tracheoesophageal fistula (OA-TOF) is a congenital digestive malformation. With improvements in surgical techniques and perioperative care, survival rates now exceed 90% and OA-TOF is no more just a neonatal surgical problem, and the focus has now shifted from mortality to morbidity with focus on long-term survival and quality of life issues. The primary complications experienced by these patients include gastroesophageal reflux, peptic and eosinophilic esophagitis, anastomotic stricture, esophageal dysmotility, abnormal gastric function, feeding difficulties and respiratory disorders including tracheomalacia and "cyanotic spells". Concerns in adults include oesophageal adenocarcinoma and epidermoid carcinoma which have been recently reported. This highlights the need for careful multidisciplinary follow up not only in childhood but also after transition to adulthood. Data regarding long-term outcomes and follow-ups are limited for patients following OA-TOF repair. The determination of the risk factors for the complicated evolution following OA-TOF repair may positively impact long-term prognoses. This e-book contains review articles and position paper on all aspects of management of this condition. The material presented in the following articles is primarily based on the presentations by world experts during the recent Fourth International Conference on Oesophageal Atresia held in Sydney in 2016.